Anthropometric and Nutritional status of Chronic Obstructive Pulmonary Disease presenting in Acute Exacerbation in Tertiary care Hospital in Eastern Nepal - Uprety, Augraj; Pantha, Srijan; Gurung, Kum Bahadur; Aryal, Prakash; Timsina, Anup; Mandal, Dipesh; Hamal, Sangita; Chaudhary, Sabnam; Thakur, Aanad Lohar; Yadav, Krishna Chandra; Shah, Nensi; Yadav, Dipendra; et al. (Nepalese Respiratory Journal, 2024)
Background: There is scarcity of data regarding the nutritional status of COPD patients presenting in exacerbation in our setup, thus this observational study was conducted. Methods: We performed an observational study of patients with acute exacerbation of COPD, who were admitted in the Department of Pulmonary, Critical care and Sleep Medicine in tertiary hospital in eastern Nepal from April 2023 to June 2023. Results: During the study period, a total of 154 patients of COPD with exacerbations were admitted in our department. The baseline anthropometric parameters, lab parameters as well as the malnutrition scores were determined. The mean BMI was 21.82 ± 3.92 kg/m2 and only 29% had BMI < 18.5 kg/m2.The mean hemoglobin, mean cell volume, serum protein, serum albumin, serum calcium, phosphorus and vitamin D level were 12.43 ± 2.32 g/dL, 84.4 ± 9.41 fL, 6.42 ± 1.74 g/ dL, 3.32 ± 0.34 g/dL, 8.98 ± 0.63 mg/dL, 3.02 ± 0.42 mg/dL, 18.48 ± 8.22 pg/mL and 40%, 12%, 28%, 41%, 31%, 42% and 49% of these values were below the lower normal limit respectively. The nutritional status tool used NRS-2002, MUST and MNAS-F screened malnutrition in about 68%, 51% and 54% respectively. There shows a discrepancy between the evaluation of the malnutrition assessed by BMI with that of nutritional assessment score. Conclusion: COPD who present in exacerbations are malnourished, but use of sole BMI to rule out malnutrition in such group of patients can cause false negative result.